Synthesis of benzothiophene and indole derivatives through metal-free propargyl–allene rearrangement and allyl migration - Yao, Jinzhong; Xie, Yajie; Zhang, Lianpeng; Li, Yujin; Zhou, Hongwei (Beilstein Journal of Organic Chemistry, 2017)
An efficient base-catalyzed protocol for the synthesis of benzothiophene is described. The reaction proceeds via base-promoted propargyl–allenyl rearrangement followed by cyclization and allyl migration. Phosphine-substituted indoles can be synthesized by a similar strategy.
Keywords: allyl migration; benzothiophene; indole; metal-free; propargyl-allenyl